2012
DOI: 10.1038/gt.2011.216
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of scAAV9 in fetal macaques facilitates neuronal transduction of the central and peripheral nervous systems

Abstract: Correction of perinatally lethal neurogenetic diseases requires efficient transduction of several cell types within the relatively inaccessible CNS. Intravenous AAV9 delivery in mouse has achieved development stage-specific transduction of neuronal cell types, with superior neuron-targeting efficiency demonstrated in prenatal compared with postnatal recipients. Because of the clinical relevance of the non-human primate (NHP) model, we investigated the ability of AAV9 to transduce the NHP CNS following intraute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 73 publications
3
56
0
Order By: Relevance
“…Consistent with mouse, rat, and cat studies, efficient gene delivery and brain transduction has been reported after systemic injection of rAAV in macaque monkeys (Bevan et al, 2011; Gray et al, 2011b; Dehay et al, 2012; Mattar et al, 2012; Samaranch et al, 2012). Even though some methodological discrepancies between studies prevent a clear comparison of the results, some conclusions can be achieved.…”
Section: Widespread Brain Transduction After Systemic Injectionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with mouse, rat, and cat studies, efficient gene delivery and brain transduction has been reported after systemic injection of rAAV in macaque monkeys (Bevan et al, 2011; Gray et al, 2011b; Dehay et al, 2012; Mattar et al, 2012; Samaranch et al, 2012). Even though some methodological discrepancies between studies prevent a clear comparison of the results, some conclusions can be achieved.…”
Section: Widespread Brain Transduction After Systemic Injectionsupporting
confidence: 72%
“…Even though some methodological discrepancies between studies prevent a clear comparison of the results, some conclusions can be achieved. Systemic administration of rAAV9 to adult monkeys induced mostly glial transduction (Bevan et al, 2011; Gray et al, 2011b; Samaranch et al, 2012) while injection in neonate animals induced neuronal transduction (Dehay et al, 2012; Mattar et al, 2012). Another concern in this field of research involves anti-AAV antibodies, which are commonly present in both non-human primate and humans (Boutin et al, 2010; Calcedo et al, 2011; Gray et al, 2011b; Samaranch et al, 2012).…”
Section: Widespread Brain Transduction After Systemic Injectionmentioning
confidence: 99%
“…Intravenous delivery is relatively noninvasive and can result in homogeneous vector distribution in the CNS. Several groups have reported on the ability of AAV9 vectors to cross the blood-brain barrier and transduce neurons and astrocytes after intravenous injection into neonatal mice, adult mice, cats, and nonhuman primates (Duque et al, 2009;Foust et al, 2009;Rahim et al, 2011;Mattar et al, 2013). However, a disadvantage of this approach is the high biodistribution of the vector to off-target peripheral tissues, thus potentially compromising the level of expression and treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Mattar et al also demonstrated efficient neuronal transduction after in utero delivery of AAV9 in non-human primates [91]. Nevertheless, this method presents significant practical concerns related to prenatal diagnostic techniques and the risks associated with the treatment [92].…”
Section: Intrauterine Administrationmentioning
confidence: 96%